Contribution of Religious Motivation and Learning Behavior to Academic Achievement of Eleventh Grade Students - Nur Izzatul Islamiyah; Adi Atmoko; Irene Maya Simon; Augusto Da Costa; Nur Izzatul Islamiyah; Adi Atmoko; Irene Maya Simon; Augusto Da Costa (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2025)
The purpose of this research is to determine the contribution of religious motivation and learning behavior to student achievement. The approach used was non-experimental quantitative with a correlational design on 120 students selected using cluster random sampling. The research instruments used have been tested for validity and reliability. The religious motivation scale has a Cronbach Alpha value of 0.833 in the very high category and the learning behavior scale has a Cronbach Alpha value of 0.680 in the high category. Learning achievement uses the average Even Semester Final Exam report card score for the 2022/2023 academic year. Data analysis used multiple regression techniques which showed an R Square value of 0.144, meaning that the two variables contributed 14.4% to the student achievement variable. The research results show; (1) religious motivation contributes to the achievement of eleventh-grade students, (2) learning behavior contributes to the achievement of eleventh-grade students, (3) religious motivation and learning behavior contribute to the achievement of eleventh-grade students. Teachers need to guide students to increase religious motivation and learning behavior to achieve the desired learning achievements.